Studies in the Syriac Magical Traditions - Bhayro, Siam; Moriggi, Marco (Magical and Religious Literature of Late Antiquity, 2022)
The study of the Syriac magical traditions has largely been marginalised within Syriac studies, with the earliest treatments displaying a disparaging attitude towards both the culture and its magical practices. Despite significant progress in more recent scholarship in respect of the culture, its magical practices and their associated literatures remain on the margins of the scholarly imagination. This volume aims to open a discussion on the history of the field, to evaluate how things have progressed, and to suggest a fruitful way forward. In doing so, this volume demonstrates the incredible riches contained within the Syriac magical traditions, and the necessity of their study.